2004
DOI: 10.1158/0008-5472.can-03-2505
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activation of p21waf1/cip1 by Alkylphospholipids

Abstract: Alkylphospholipids (ALKs) are a novel class of antitumor agents with an unknown mechanism of action. The first ALK tested in the clinic, miltefosine, has been approved recently in Europe for the local treatment of patients with cutaneous metastasis. Perifosine, the only available oral ALK, is being studied currently in human cancer clinical trials. We have shown previously that perifosine induces p21 waf1/cip1 in a p53-independent fashion and that induction of p21 waf1/cip1 is required for the perifosineinduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 70 publications
1
17
1
Order By: Relevance
“…Waf/Cip1 promoter and urokinase are the targets of the MAP kinase/Erk kinase signaling pathway, suggesting that Sp1 recognition of the GC-box sites might be the target of MAP kinase/Erk kinase signaling (36,37). Because controlling DNA binding and protein interactions with the corepressors via ZFDBD or ID could be important functions in regulating Sp1 activity, it was assumed that the molecular interactions between Sp1 and the corepressors might be the target of the MAP kinase signaling pathway, which could thereby regulate the transcription of the Sp1-dependent promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waf/Cip1 promoter and urokinase are the targets of the MAP kinase/Erk kinase signaling pathway, suggesting that Sp1 recognition of the GC-box sites might be the target of MAP kinase/Erk kinase signaling (36,37). Because controlling DNA binding and protein interactions with the corepressors via ZFDBD or ID could be important functions in regulating Sp1 activity, it was assumed that the molecular interactions between Sp1 and the corepressors might be the target of the MAP kinase signaling pathway, which could thereby regulate the transcription of the Sp1-dependent promoters.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that MEK, from the MAP kinase pathway, phosphorylates Sp1 at amino acids 453 and 739 (36,38,40). The phosphorylation of these two sites results in an increase in Sp1 binding to the target sites and in increased transcription activation.…”
Section: Waf/cip1mentioning
confidence: 99%
“…Cells were cotransfected with 10 ng/well of wild-type mouse ER␣ or mutant nonclassical ER E207A/G208A (AA) expression vector and 500 ng/well of the indicated reporter constructs (AP-1-luciferase or p21-luciferase) using Lipofectamine 2000 (Invitrogen) according to the manufacturer's instructions. The 2.4-kb full-length human p21 reporter was kindly provided by Dr. Xiao-Fan Wang (Duke University) (21,22). The ER expression and AP-1 reporter constructs have been previously described (11,15).…”
Section: Methodsmentioning
confidence: 99%
“…The transcription factor SP1 plays a role in ERK-mediated p21 transcription in various cell types, including nerve growth factor-treated PC12 cells (60), Ras-transformed NIH3T3 cells (61), alkylphospholipid-treated HaCaT cells (33), and arsenic trioxide-exposed A431 epidermoid carcinoma cells (62). ETS and C/EBP␤ (63) are also involved in ERK-dependent, p53-independent expression of p21 expression in primary hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, ERK contributes to the induction of neuronal differentiation by nerve growth factor (29) and to growth arrest and the induction of apoptosis through phosphoactivation of p53 (30,31). Elsewhere, several studies have demonstrated that ERK signaling is associated with up-regulation of p21 expression in a variety of cell types (32)(33)(34)(35)(36)(37)(38). However, despite the emerging recognition that MAPKs inhibit cell proliferation by affecting p21 expression, little is yet known about the mechanisms by which these kinases regulate p21 transcription.…”
mentioning
confidence: 99%